Improving Bandwidth of Yagi-Uda Arrays - Formato, Richard A. (Scientific Research Publishing, 2012)
A novel approach for improving antenna bandwidth is described using a 6-element Yagi-Uda array as an example. The new approach applies Central Force Optimization, a deterministic metaheuristic, and Variable Z0 technology, a novel, proprietary design and optimization methodology, to produce an array with 33.09% fractional impedance bandwidth. This array’s performance is compared to its CFO-optimized Fixed Z0counterpart, and to the performance of a 6-ele- ment Dominating Cone Line Search-optimized array. Both CFO-optimized antennas exhibit better performance than the DCLS array, especially with respect to impedance bandwidth. Although the Yagi-Uda antenna was chosen to illustrate this new approach to antenna design and optimization, the methodology is entirely general and can be applied to any antenna against any set of performance objectives.
Keywords: Characteristic Impedance; Feed System; Antenna; Antenna Design; Antenna Optimization; Design Objectives; Performance Objectives; Bandwidth; Impedance Bandwidth; Broadband; Ultra Wideband; UWB; Yagi; Yagi-Uda; Central Force Optimization; CFO; Numerical Optimization; Optimization Algorithm; Metaheuristic; Dominating Cone Line Search; DCLS; Variable Z0, Z0